Immersió lingüística a Catalunya, identitat i imatge - Perera, Santiago; -, Arantza del Valle; Monreal, Pilar; Vila, Ignasi (Caplletra. Revista Internacional de Filologia, 1996)
The authors analyze the question of whether there is a mimetic correlation between the conservation of Catalan and the maintenance of a cultural and national identity. They study the self-inclusion, if any, of youths between six and fifteen years of age in national groups -Catalan or Spanish- according to the language spoken at home and at school, together with the images and feelings they construe in relation to other European national groups.